What Hat Goes with That? - Chanko & Michael; Childrens Press (New York, N.Y.) (New York, NY Childrens Press, an imprint of Scholastic Inc., 2017)
Simple text and colorful illustrations discuss which hat to wear for each activity, including playing in the snow, going to a birthday party, cooking, and playing in the sand.
Keywords: Hats -- Juvenile literature; Clothing and dress -- Juvenile literature; Board books -- Juvenile fiction